Cost-Effectiveness of Robotic vs. Laparoscopic Surgery for Different Surgical Procedures: Protocol for a Prospective, Multicentric Study (ROBOCOSTES) - Ielpo, Benedetto; Podda, Mauro; Burdio, Fernando; Sanchez-Velazquez, Patricia; Guerrero, Maria-Alejandra; Nuñez, Javier; Toledano, Miguel; Morales-Conde, Salvador; Mayol, Julio; Lopez-Cano, Manuel; Espín-Basany, Eloy; Pellino, Gianluca; et al. (Frontiers in Surgery, 2022)
Background The studies which address the impact of costs of robotic vs laparoscopic approach on quality of life (cost-effectiveness studies) are scares in general surgery. Methods The Spanish national study on cost-effectiveness differences among robotic and laparo-scopic surgery (ROBOCOSTES) is designed as a prospective, multicentre, national, obser-vational study. The aim is to determine in which procedures robotic surgery is more cost-effective than laparoscopic surgery. Several surgical operations and patient populations will be evaluated (distal pancreatectomy, gastrectomy, sleeve gastrectomy, inguinal hernioplasty, rectal re-section for cancer, Heller cardiomiotomy and Nissen procedure). Discussion The results of this study will demonstrate which treatment (laparoscopic or robotic) and in which population is more cost-effective. This study will also assess the impact of previous surgical experience on main outcomes.